OENELUSURAN "ATURAN MAIN" PEMBIAYAAN MIKRO KECIL MENENGAH DALAM KONTEKS PERSAINGAN ANTAR LEMBAGA - Tyas Danarti; Asfi Manzilati; Nurul Badriyah (Jurnal Keuangan dan Perbankan, 2010)
The purpose of this study was how the regulations concerning the financing insti-tutions (rules or rules of play and supervision), how the reality of system or mechanism foreach financial institution referred to in channeling financing to small and medium segment,and on turn, how the impact of these two issues of competition among the existing financ-ing institutions. With in-depth observation and interviews, we found that formally Bank ofIndonesia only act as mediators between the SMEs and business actors such financial institu-tions through training, meeting facilitation for coordination and delivery of information;implications of the operational rules of the microfinance institutions can be divided intofour important issues, those are the target market, the mechanism of realization of loans,settlement mechanism of risk, and strategies to face competition; and the absence of clearrules or boundaries for the operation of financial institutions, in turn, a uniform servicedelivery and increasing competition tightened and increased the risk to the financial institu-tions themselves and for society.